Empirical research in clinical ethics: The ‘committed researcher’ approach - Fournier, Véronique (Bioethics, 2020)
After the ‘empirical turn’ in bioethics, few specific approaches have been developed for doing clinical ethics research in close connection with clinical decision-making on a daily basis. In this paper we describe the ‘committed researcher’ approach to research in clinical ethics that we have developed over the years. After comparing it to two similar research methodological approaches, the ‘embedded researcher’ and ‘deliberative engagement’, we highlight its main features: it is patient-oriented, it is implemented by collegial and multidisciplinary teams, it uses an ethical grid to build the interview guide, and it is geared towards bringing the results to bear on the public debate surrounding the issue at stake. Finally, we position our methodological approach with respect to the ‘is vs. ought’ distinction. We argue that our ‘commitment researcher’ approach to clinical ethics research takes concerned people’s life-building values as the main data, and compares them to the larger normative framework underlying the medical practice at stake.